Soil management and soil microbial activity in dark red latosol from Sete Lagoas region, MG, Brazil - Vasconcellos, Carlos Alberto; Hermeto Dias Figueiredo, Ana Paola; Evangelista de França, Gonçalo; Coelho, Antônio Marcos; Bressan, Wellignton (Pesquisa Agropecuaria Brasileira, 1998)
The aim of this work was to study the influence of soil management practices on the microbial activity in dystrophic dark red latosol. Soil samples were collected from the following: 1. areas cultivated with green manure; 2. areas cultivated with maize and bean rotation with no till; 3. grain sorghum; and 4. maize for silage and beans rotation with conventional soil management (plowing and harrowing). The water pH of those samples ranged from 5.5 to 6.6. The soil samples were incubated for up to 75 days at 25°C, with and without maize stalk residue applied at 10 t/ha rate. The CO2 evolved, the mineral N and the biomass N were determined. The biomass was calculated from the difference between the N extracted by potassium sulfate 0.5N from chloroform fumigated and unfumigated samples. The results demonstrated that the incorporation of an energy source decreased the biomass N by 50 mg/g of soil. However this reduction was influenced by soil management. Without maize straw the CO2 evolved showed a positive correlation with pH. With straw, CO2 evolution was smaller in no-till system and the pH correlation was not observed.